2021
DOI: 10.1007/978-3-030-50200-3_20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manner Adverbs on Action Verb Processing

Abstract: Language-motor interaction is suggested by the involvement of motor areas in action-related language processing. In a double-dissociation paradigm we aimed to investigate motor cortical involvement in the processing of hand- and foot-related action verbs combined with manner adverbs. In two experiments using different tasks, subjects were instructed to respond with their hand or foot following the presentation of an adverb-verb combination. Experiment 1, which prompted reactions via color changes of the stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
2
1
0
Order By: Relevance
“…The slower verb recognition in the slow speed condition indicated again that the context can modulate the simulation speed. This result was somewhat in agreement with previous studies indicating that the action simulation in verb processing is flexible ( Bidet-Ildei et al, 2017b ; Sieksmeyer et al, 2021 ). And this result might be attributed to the fact that the originally less certain speed information implied in verbs can be specified by the context.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The slower verb recognition in the slow speed condition indicated again that the context can modulate the simulation speed. This result was somewhat in agreement with previous studies indicating that the action simulation in verb processing is flexible ( Bidet-Ildei et al, 2017b ; Sieksmeyer et al, 2021 ). And this result might be attributed to the fact that the originally less certain speed information implied in verbs can be specified by the context.…”
Section: Resultssupporting
confidence: 94%
“…The facilitated verb recognition in the first-person perspective fast action sentences compared with that in the first-person perspective slow action sentences seemed to be consistent with previous research which found that action simulation can be modulated by semantic context (e.g., Moody and Gennari, 2010 ; Bidet-Ildei et al, 2017a ; Sieksmeyer et al, 2021 ). One possible explanation for this might be that the fast action sentences were more semantically plausible and familiar than the slow action sentences.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation